Las rondas infantiles y la motricidad gruesa en los niños del nivel inicial II de la Escuela de Educación Básica Alonso de Mercadillo de la ciudad de Loja, periodo 2021-2022 - Macas Saca, Nancy Alexandra (2022)
The gross motor area has to do with movements of the different muscles of the body from head to toe, it seeks to stimulate the upper and lower extremities, where thanks to its coordination, the child can maintain good posture, move around and move around allowing them to achieve efficient development when performing daily functions, strengthening development. The objective of the research was to determine how children’s rounds help in gross motor skills in children of initial level II of the Alonso de Mercadillo School of Basic Education in the city of Loja in the period 2021-2022. The design that was used was quasi-experimental when performing a moderate intervention in the independent variable, in the same way among the methods used was the analytical-synthetic, which allowed analyzing and synthesizing the most important information within the theoretical framework, and the inductive-deductive, helped to meet the proposed objectives, by building knowledge and establishing recommendations and conclusions; the technique used was an interview, addressed to the teacher of initial level II, and the instrument applied was the Cruz and Mazaira psychomotor evaluation scale that evaluated the individual psychomotor development of 16 children considered in the investigation, where the results determined that 95% were at the low and normal level of the activities proposed for the development of the gross motor area, but after applying the guide based on the children’s rounds, it was shown that 86% managed to advance to a good level by performing well everything set. It is important to argue that the children’s rounds contributed effectively to gross motor skills, demonstrating participation by the children in a pleasant way, with respect, enthusiasm, and in this way, they were acquiring knowledge, effective physical skills, benefiting balance, coordination, strength and body scheme. Keywords: physical skills, gross motor skills, children's rounds, types of children's rounds.